2005
DOI: 10.1002/pon.934
|View full text |Cite
|
Sign up to set email alerts
|

Social‐cognitive correlates of adjustment to prostate cancer

Abstract: SUMMARYThis study examined whether social support might enhance health-related quality of life in men (n = 89) treated for localized prostate cancer by improving their ability to cognitively process their cancer experience. Data were collected using two, structured in-person interviews and abstracting medical records. The baseline interview was within several months (T1) after treatment for cancer, and follow-up was 3 months later (T2). Most men (61.8%) were treated by radical prostatectomy. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 55 publications
6
85
1
3
Order By: Relevance
“…Further, the majority of the sample (59.3%) reported depressive symptoms above the clinical cutoff score (≥10). Reported levels of negative cancer-related intrusive thoughts, although low, were consistent with previous research with men with cancer [26].…”
Section: Sociodemographic and Cancer-related Predictors Of Sleep Qualitysupporting
confidence: 78%
“…Further, the majority of the sample (59.3%) reported depressive symptoms above the clinical cutoff score (≥10). Reported levels of negative cancer-related intrusive thoughts, although low, were consistent with previous research with men with cancer [26].…”
Section: Sociodemographic and Cancer-related Predictors Of Sleep Qualitysupporting
confidence: 78%
“…For these reasons, and for many others, the experience of prostate cancer is uniquely stressful; and social support has been demonstrated to be beneficial in coping with prostate cancer's associated stressors (Roberts et al, 2006). Social support for many individuals is an intuitive term that is used to describe help that is received from others in a difficult situation.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies on cancer patients have found that meaning-focused strategies, such as positive reframing, are related to better subsequent adjustment, such as improved quality of life and psychological wellbeing [35,36], others have reported that searching for meaning is related to poorer adjustment [37,38]. The results of this study show that a brief meaning-focused intervention effectively improves the level of existential wellbeing and quality of life of advanced cancer patients, especially in older people, patients who received inadequate palliative care services and who lack social support, and newly diagnosed patients in the advanced stage of illness.…”
Section: Discussionmentioning
confidence: 99%